Karachi, You're Killing Me! - Saba Imtiaz (London VINTAGE, 2014)
Ayesha is a twenty-something reporter in one of the world's most dangerous cities. Her assignments range from showing up at bomb sites and picking her way through scattered body parts to interviewing her boss's niece, the couture-cupcake designer. In between dicing with death and absurdity, Ayesha despairs over the likelihood of ever meeting a nice guy, someone like her old friend Saad, whose shoulder she cries on after every romantic misadventure. Her choices seem limited to narcissistic, adrenaline-chasing reporters who'll do anything to get their next story, to the spoilt offspring of the Karachi elite who'll do anything to cure their boredom. Her most pressing problem, however, is how to straighten her hair during the chronic power outages. Karachi, You're Killing Me! is Bridget Jones's Diary meets the Diary of a Social Butterfly, a comedy of manners in a city with none.
English Fiction.
Keywords: Karachi - Pakistan -- Karachi -- Pakistan